Biolubricant Production of 2‐Ethylhexyl Palmitate by Transesterification Over Unsupported Potassium Carbonate. (28th February 2018) - Zheng, Ting; Wu, Zhenyu; Xie, Qinglong; Lu, Meizhen; Xia, Fan; Wang, Guangquan; Nie, Yong; Ji, Jianbing
Abstract: Owing to the decrease of global oil price, development of downstream value‐added products is important to biodiesel industry. In this study, we used palmitic acid methyl ester (PAME) as a starting material to produce 2‐ethylhexyl palmitate (2‐EHP), an environmentally friendly biolubricant product, which was derived from the transesterification of fatty acid methyl esters and long chain fatty alcohols. Conventional synthetic routes of 2‐EHP have disadvantages, including high catalyst price, low conversion efficiency, and pollution issues. To solve these problems, in situ transesterification of PAME with 2‐ethylhexanol (2‐EH) was conducted over unsupported potassium carbonate as heterogeneous catalyst. The optimal reaction temperature, 2‐EH to PAME molar ratio, and catalyst to PAME mass ratio were 180 °C, 3:1, and 3.0 wt%, respectively. The PAME conversion reached up to 100% within 1 hour under the optimal conditions. In addition, a kinetic model describing the experimental data over a temperature range of 160–180 °C was developed. The dependence of kinetic rate constant ( k ) on temperature was evaluated, and the activation energy ( E a ) for the transesterification of PAME with 2‐EH was calculated to be 57.04 kJ mol −1 .